STRENGTHENING MARKETPLACE-BASED BRANDING AND MARKETING THROUGH A DIGITAL MENTORING APPROACH TO IMPROVE THE PERFORMANCE OF JAN ENDOLS COOKIES MSMES IN SIDOARJO REGENCY - Dara Anindya Putri Umagapi; Achmad Nuril Huda; Agus Hermawan; Agung Winarno (RADJA PUBLIKA, 2025)
The Jan Endols Dry Cake MSME in Sidoarjo Regency is a custom-made culinary business still managed conventionally, particularly in operational management and marketing strategies. This situation limits business efficiency and market reach, making digitalization a strategic necessity to increase competitiveness. This community service activity aims to strengthen the management and marketing of MSMEs through digital-based mentoring. The mentoring is carried out in a participatory and implementative manner through stages of observation, problem identification, training, and monitoring and evaluation tailored to the needs and capacities of business actors. The mentoring focuses on implementing simple digital financial records, managing orders and production processes, and utilizing social media and marketplaces as marketing tools. The activity results show increased operational efficiency, expanded marketing reach, and an increased understanding and ability of MSMEs in utilizing digital technology. These findings confirm that digital mentoring has significant potential to support the strengthening of management, marketing, and sustainability of culinary MSMEs at the local level, while also serving as a mentoring model for other MSMEs with similar characteristics.